A procedural perspective on academic spin-off creation: The changing relevance of academic and commercial logics - Uwe Cantner; Philip Doerr; Maximilian Göthner; Matthias Huegel; Martin Kalthaus (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2021)
We analyze the influence of two contradicting settings on the success in the academic spin-off creation process. Scientists, who are embedded in the academic setting, have to reach out and adapt to the logics of the commercial setting to successfully found their firm. However, along this process, many scientists fail because they cannot overcome the contradictions between these logics. We provide the first empirical evidence on the relevance of these two contradicting logics along the spin-off creation process. Based on a phase-based conceptualization of the spin-off process, we hypothesize a decreasing relevance of the academic setting and an increasing relevance of the commercial setting for successful transitions between the process phases. We test these relationships with a representative sample of German scientists using dominance analysis to determine the relative importance of the two settings. Our findings show a decreasing relative importance of the academic setting along the spin-off creation process, in line with our hypotheses. The relevance of the commercial setting initially increases before it decreases in the latest stage of the process, contrary to our hypothesis. Additionally, we find that the commercial setting is generally more important than the academic setting, especially in the beginning of the process. Our results provide a deepened understanding of the academic spin-off creation process and extend existing theories. Furthermore, they provides intervention points for policy along the spin-off creation process.
Keywords: L26; O31; O33; 330; Academic Entrepreneurship; Transition Process; Phase Model; Dominance Analysis